2006
DOI: 10.1063/1.2194227
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oxygen supply during growth on the electrical properties of crystalline Gd2O3 thin films on Si(001)

Abstract: We investigated the influence of additional oxygen supply and temperature during the growth of thin Gd2O3 layers on Si(001) with molecular beam epitaxy. Additional oxygen supply during growth improves the dielectric properties significantly; however, too high oxygen partial pressures lead to an increase in the lower permittivity interfacial layer thickness. The growth temperature mainly influences the dielectric gate stack properties due to changes of the Gd2O3∕Si interface structure. Optimized conditions (600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(61 citation statements)
references
References 15 publications
3
58
0
Order By: Relevance
“…Capacitance/voltage (C-V) data of metal-insulator-semiconductor (MIS) capacitors with 12.5 AE 0.5 nm thick Gd x Al 2- The permittivity was found to increase with Gd content, in keeping with the permittivity values reported for Al 2 O 3 (k $ 8) [42] and Gd 2 O 3 (typically 14-16, [18,19,25,43,44] although higher values up to 24 have also been reported for epitaxial layers [45] [12,13,46] where no large decrease of Full Paper the permittivity with respect to La 2 O 3 was also observed, neither due to Al 2 O 3 incorporation [47] nor due to amorphization. [48] 3.…”
Section: à3supporting
confidence: 81%
“…Capacitance/voltage (C-V) data of metal-insulator-semiconductor (MIS) capacitors with 12.5 AE 0.5 nm thick Gd x Al 2- The permittivity was found to increase with Gd content, in keeping with the permittivity values reported for Al 2 O 3 (k $ 8) [42] and Gd 2 O 3 (typically 14-16, [18,19,25,43,44] although higher values up to 24 have also been reported for epitaxial layers [45] [12,13,46] where no large decrease of Full Paper the permittivity with respect to La 2 O 3 was also observed, neither due to Al 2 O 3 incorporation [47] nor due to amorphization. [48] 3.…”
Section: à3supporting
confidence: 81%
“…The gap states which are strongly localized on the orbitals of the adjacent metal ions can result in significant increase in the leakage current conduction [18,28]. Further, if the V Os related defect states give rise to mobile oxide charges, they can result in flat band instability causing hysteretic C-V behaviour when a MOS capacitor is subjected to an external electric field [13]. One way of reducing the V Os in complex oxides is to grow the oxide thin films at sufficiently high 2 O P [13,29].…”
Section: Xps Investigationmentioning
confidence: 99%
“…Further, if the V Os related defect states give rise to mobile oxide charges, they can result in flat band instability causing hysteretic C-V behaviour when a MOS capacitor is subjected to an external electric field [13]. One way of reducing the V Os in complex oxides is to grow the oxide thin films at sufficiently high 2 O P [13,29]. However, our experiments indicated that increasing 2 O P beyond ~5-8×10 -7 mbar does not significantly improve the dielectric properties, which could be related to the incomplete annihilation of V Os by increasing oxygen chemical potential [30].…”
Section: Xps Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…During the layer growth, additional molecular oxygen was supplied into the chamber due to the oxygen deficiency in the rare-earth oxides evaporated by electron beam. 9,10) The substrate temperature was set to 948 K and the partial pressure of oxygen was kept at 5 Â 10 À7 mbar, which was controlled by a piezo leak valve. Crystal structures of the grown oxides were examined along the out-of-plane, in-plane, and asymmetric reciprocal space directions, as schematically shown in Fig.…”
Section: Methodsmentioning
confidence: 99%